Os sentidos da experiência escolar para jovens do ensino médio: um estudo em três escolas na cidade de Caxias do Sul/RS - Schlickmann, Vitor (2013)
This thesis fits into the theme Youth Culture and School Culture, in the Research Line - School Practice and Public Policy, in the Graduate Program in Education at the Federal University of Santa Maria UFSM/RS. The research aimed to understand how teenagers establish relationships of meaning regarding the school experience lived during High School. In this way, the work has as a general objective to analyze the experiences they consider important about their school experience of High School. The specific objectives aim to understand how school interacts with the students cultures at school; to analyze, from the perspective of the students, the meanings of school in their lives; to research the students motivations when attending school and finally, to analyze the experiences that assess how important experienced in high school about school. The thesis is based on the hypothesis that the current conditions of high school by themselves do not offer meanings for the teenagers. Each one must elaborate on his/her own experiences. The collaborators selected for this study are from three (03) High Schools (third year, one class from each school), in the city of Caxias do Sul: two (02) of them are public state schools - one (01) of them is located downtown -, and the third one is a private school. The research developed a qualitative study through written reports by the students, who wrote e-mails about their experiences at high school, about what they consider important to learn in this level of education and their experiences. It is used textual discourse analysis for this investigation. The theoretical basis comes from Dubet s sociological contributions and some theoretical analyzes from numerous researchers of education and sociology that contribute to the understanding of high school and youth cultures present in schools. The school in presented perspective, a major source of socialization, understood as a continuous process of training and preparation of social subjects, which are put into play different attributes for life in society. Although some students cite a passion for studies, like studying, this manifestation is timid compared to most of the writings of the young. Those are prevalent in school obligation, or in view of future projects, or to continue their studies or to enter the working world. Young people highlight the importance of "getting along in school," to attend a good school, get a good education.